High-accuracy spectropolarimetric study of γ Pegasi in the line He I 6678 Å - Butkovskaya, V.; Khan, S.; Plachinda, S.; Rostopchin, S.; Shulyak, D. (Известия Крымской астрофизической обсерватории, 2007)
Results of an intensive spectropolarimetric study of the small-amplitude purely radial pulsating β Cephei-type star γ Pegasi are presented. It was found that residual intensity, full width at half maximum and equivalent width of the helium line vary during 0.15-day pulsation period and reach its maximal value when the temperature of the star is highest. The line parameter variations due to pulsation were explained as a temperature effect. It was shown, that if the star has a dipole magnetic field then dipole axis would be situated near rotation equator plane. It was estimated, that owing to frizzing of magnetic field into plasma amplitude of the longitudinal magnetic field variation due to radial pulsation of the star is 0.4 Gauss. Studying of a possible origin of 6.83-day period of γ-velocity variation has been made. It was concluded, that the star is a spectroscopic binary and improved orbital elements are presented. The orbit inclination angle was estimated as i ≤ 7°.